Status terkini Covid-19 Malaysia : ringkasan kes kematian baharu (03.09.2021) - Malaysia, Kementerian Kesihatan (Kementerian Kesihatan Malaysia (KKM), 2022)
This item is made available on Ministry of Health Malaysia, Covid-19 homepage at http://covid-19.moh.gov.my/